2021
DOI: 10.3390/toxins13110811
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of Aripiprazole to Plasma Proteins in Chronic Renal Failure Patients

Abstract: The binding of drugs to plasma protein is frequently altered in certain types of renal diseases. We recently reported on the effects of oxidation and uremic toxins on the binding of aripiprazole (ARP) to human serum albumin. In our continuing investigations, we examined the binding of ARP to plasma pooled from patients with chronic renal dysfunction. We examined the issue of the molecular basis for which factors affect the changes in drug binding that accompany renal failure. The study was based on the statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For aripiprazole, the equivalent calculation – 180 ng/ml and 0.64% unbound (Hirata 2021) – yields 2.57 nM free drug from which, with a K d of 0.34 nM (Burris 2002), an occupancy of 88.3% is again calculated.…”
Section: Quantitative Examplesmentioning
confidence: 99%
“…For aripiprazole, the equivalent calculation – 180 ng/ml and 0.64% unbound (Hirata 2021) – yields 2.57 nM free drug from which, with a K d of 0.34 nM (Burris 2002), an occupancy of 88.3% is again calculated.…”
Section: Quantitative Examplesmentioning
confidence: 99%
“…The binding of aripiprazole in the cases of renal failure was reduced significantly, compared with the same values for healthy adults. An association was found between the ARP binding rate and the concentration of toxins, including IS and PCS [ 62 ].…”
Section: Interaction Between Uremic Toxins and Albuminmentioning
confidence: 99%
“…We recently studied the binding properties of ARP derivatives to plasma proteins as part of a preliminary pharmacokinetic evaluation of these molecules. ARP binds to human serum albumin (HSA) and the α 1 -acid glycoprotein. ARP binds more strongly to HSA than the other ARP derivatives, and the binding affinity of ARP to HSA (5.94 × 10 6 M –1 ) is more than 50 times higher than that of deschloro-ARP (0.10 × 10 6 M –1 ) . We determined the crystal structure of HSA complexed with ARP, and the results indicated that the binding position of ARP overlaps with the fatty acid binding sites 3 and 4 in HSA .…”
Section: Introductionmentioning
confidence: 99%